(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
The article is devoted to foreign experience in the organization of management and regulation in the field of housing and communal services market. The author analyzes the possibilities of regulation and management of housing and communal services abroad; The experience of reforms implemented in the development of Western European countries is studied; possibilities of using foreign experience in reforming the local housing and communal sector were determined. Based on the analyzes carried out in the article, specific recommendations are given to increase the role of self-management bodies of the population in the management of this sector, and to improve the quality of providing housing and communal services to the population.